2021
DOI: 10.7759/cureus.17275
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vancomycin Mixed Bone Graft and Vancomycin Mixed Saline Wash Before Wound Closure Reduces the Rate of Infection in Lumbar Spine Fusion Surgery

Abstract: This study aims to evaluate whether surgical site vancomycin mixed in bone grafts and local vancomycin mixed in normal saline wash before wound closure decrease the infection rates in patients undergoing lumbar spinal instrumentation and posterolateral fusion. A retrospective study was performed on cases between 2017 and 2019, who underwent lumbar spine instrumentation and posterolateral fusion for lumbar canal stenosis or listhesis. The routine prophylactic procedures were performed in all patients as per ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…There have been many articles on the topical of local vancomycin to reduce the risk of infection after orthopaedic surgery [3,38,39]. Moreover, vancomycin impregnated bone graft has been also widely used in spinal surgery [40][41][42]. Therefore, a prospective randomized study with an adequate patient number is needed to clarify the benefits of vancomycin impregnated autogenous bone graft and bone substitute on preventing DSSI following degenerative lumbar spine fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many articles on the topical of local vancomycin to reduce the risk of infection after orthopaedic surgery [3,38,39]. Moreover, vancomycin impregnated bone graft has been also widely used in spinal surgery [40][41][42]. Therefore, a prospective randomized study with an adequate patient number is needed to clarify the benefits of vancomycin impregnated autogenous bone graft and bone substitute on preventing DSSI following degenerative lumbar spine fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study also reported significantly reduced arthrodesis in the vancomycin-loaded cohort and proposed the utility of vancomycin-loaded demineralized bone matrix as an extension of iliac bone crest autograft [17] . Multiple retrospective clinical studies of infection in spinal fusion surgery have also demonstrated the effectiveness of vancomycin impregnation in autologous bone grafts to prevent infection [ 31 , 32 ]. However, the use of antibiotic-loaded bone grafts is currently not standard in spinal or orthopedic applications due to the possible impairment of osteoblast differentiation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%